Characteristics of men who have sex with men and transgender women in Myanmar who test frequently for HIV - Vanessa Veronese; Zaw Min Oo; Zaw Win Thein; Bridget Draper; Poe Poe Aung; Claire Ryan; Myo Thant; Chad Hughes; Mark Stoové (Inishmore Laser Scientific Publishing Ltd, 2018)
# Background HIV prevalence among men who have sex with men (MSM) and transgender women (TW) in Myanmar is increasing and less than half report having a HIV test in the past 12 months. The promotion of regular testing among this group has been identified as a key priority of the national HIV response, yet there remains limited information on HIV testing patterns and frequency among MSM and TW. # Methods A cross-sectional quantitative survey was conducted among self-identifying MSM and TW in November 2015 recruited from known hot-spot locations in Yangon and Mandalay to characterise the self-reported HIV testing frequencies among MSM and TW and explore factors associated with high frequency HIV testing. # Results Among 353 HIV negative or unknown MSM and TW, more than half were identified as high frequency testers based on their regular HIV testing routine and date of last HIV test; this was significantly associated with reporting recent sex with regular male partners and location of last HIV test. # Conclusion Our findings contrast with national data suggesting sub-optimal testing uptake and support HIV testing delivered through community-based, tailored HIV testing services and the role of such models in establishing and maintaining regular HIV testing behaviours among MSM and TW in Myanmar.